2009
DOI: 10.1002/stem.257
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Strategy for Single and Combinatorial Analysis of miRNA Function in Mammalian Hematopoietic Stem Cells

Abstract: The regulatory role of micro-RNAs (miRNAs) in hematopoietic development is increasingly appreciated. Reverse genetics strategies based on the targeted disruption of miRNAs offer a powerful tool to study miRNA functions in mammalian hematopoiesis. The miR-144/451 cluster comprises two miRNAs coexpressed from a common precursor transcript in an erythroid-specific manner. To decipher the contribution of each miRNA of the cluster in mammalian erythropoiesis, we developed a strategy for stable in vivo individual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 58 publications
4
92
1
Order By: Relevance
“…Discussion miR-144/451 is strongly induced during erythropoiesis in zebrafish, mice, and humans (Kloosterman et al 2006;Choong et al 2007;Masaki et al 2007;Zhan et al 2007;Dore et al 2008;Du et al 2009), and artificial manipulation of these miRNAs alters erythroid maturation in several experimental models (Zhan et al 2007;Dore et al 2008;Pase et al 2009;Papapetrou et al 2010). Here we report the consequences of miR-144/451 ablation in mice, and further investigations into the effects of miR-451 depletion in zebrafish.…”
Section: Enforced Expression Of 14-3-3z Inhibits Nuclear Accumulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion miR-144/451 is strongly induced during erythropoiesis in zebrafish, mice, and humans (Kloosterman et al 2006;Choong et al 2007;Masaki et al 2007;Zhan et al 2007;Dore et al 2008;Du et al 2009), and artificial manipulation of these miRNAs alters erythroid maturation in several experimental models (Zhan et al 2007;Dore et al 2008;Pase et al 2009;Papapetrou et al 2010). Here we report the consequences of miR-144/451 ablation in mice, and further investigations into the effects of miR-451 depletion in zebrafish.…”
Section: Enforced Expression Of 14-3-3z Inhibits Nuclear Accumulationmentioning
confidence: 99%
“…These miRNAs are strongly induced during zebrafish, mouse, and human erythroid maturation (Bruchova et al 2007;Choong et al 2007;Masaki et al 2007;Zhan et al 2007;Dore et al 2008;Merkerova et al 2008;Du et al 2009;Fu et al 2009;Pase et al 2009;Papapetrou et al 2010). miR-451 is also present in mature circulating red blood cells (Kloosterman et al 2006;Rathjen et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-451 augments dimethyl sulfoxide-induced erythroid differentiation in MEL cells (11). Conversely, loss-of-function of miR-144/451 impedes erythroid maturation in MEL cells (4), in zebrafish embryos (4,6,34), and in mice (9,35). miR-144 has been shown to negatively regulate a-hemoglobin expression and form a feedback circuitry in fine-turning of its expression (13).…”
Section: Mir-451 In Erythropoiesismentioning
confidence: 99%
“…(Barbato, et al, 2010) Both miR-144 and miR-451 were found to be required for erythropoiesis in bone marrow reconstitution experiments 3-4 weeks after transplantation of cells expressing miRNA sponges. (Papapetrou, et al, 2010) …”
Section: Targeting Mirna Expression To Modulate Gene Expressionmentioning
confidence: 99%